Spatially Confined Assembly of Monodisperse Ruthenium Nanoclusters in a Hierarchically Ordered Carbon Electrode for Efficient Hydrogen Evolution. (14th April 2018) - Wang, Zhong‐Li; Sun, Keju; Henzie, Joel; Hao, Xianfeng; Li, Cuiling; Takei, Toshiaki; Kang, Yong‐Mook; Yamauchi, Yusuke
Abstract: The redox units of polyaniline (PAni) are used cooperatively, and in situ, to assemble ruthenium (Ru) nanoclusters in a hierarchically ordered carbon electrode. The oxidized quinonoid imine (QI) units in PAni bond Ru complex ions selectively, whereas reduced benzenoid amine (BA) units cannot. By electrochemically tuning the ratio of QI to BA, Ru complexes are spatially confined in the outer layer of hierarchical PAni frameworks. Carbonization of Ru‐PAni hybrids induces nucleation on the outer surface of the carbon support, generating nearly monodisperse Ru nanoclusters. The optimized catalyst has a low loading of approximately 2 wt % Ru, but exhibits a mass activity for the hydrogen evolution reaction that is about 6.8 times better than commercial 20 wt % Pt/C catalyst.